Comparative and quantitative estimation of macronutrients in six different Banana varieties (Musa Spp) consumed in Jaffna - Jayawadhana, R.P.L.S.; Rajkumar, G. (University of Jaffna, 2021)
Banana, fruit of the genus Musa, one of the most important fruit crops in many developing countries in terms of per capita consumption. This research aims to compare the general nutrient composition of selected six different banana varieties available in Jaffna; Sevvalai (red banana), Etharai, Kathali, Kappal, Anaivalai and Sambal. Proximate nutrient content of banana varieties was estimated according to the standard protocols recommended by the Association of Analytical Chemists (AOAC) and compared the general nutrient composition among them. Banana has moisture contents varied from 73.85 % (Red banana) to 77.72 % (Kathali), ash contents varied from 0.55 % (Anaivalai) to 1.58 % (Kappal), fat contents ranged from 0.35 % (Etharai) to 4.70 % (Anaivalai), protein contents varied from 2.04 % (Etharai) to 8.11 % (Sambal), and carbohydrate contents varied from 12.13 % (Sambal) to 21.38 % (Sevvalai). Moisture content of all six banana varieties is almost similar. In banana varieties analysed, Sambal variety possess some desirable nutritional attributes than other banana varieties with respect to higher protein, ash content and lower carbohydrate content followed by Kappal variety.
Keywords: Banana; Fat; Carbohydrate; Protein; Ash; Monsture